Ethanolic Extract of the Root of Asparagus Racemosus as a Potential Anthelmintic Agent against Gastrointestinal Nematodes in Goats - Pandey, Arjun (NPRC Journal of Multidisciplinary Research, 2025)
Background: Asparagus racemosus (AR) plant was traditionally used as deworming remedy. The present study was aimed to investigate the anthelminthic activity of ethanolic extract of AR root (EEAR) against gastrointestinal nematodes in goats. Methods: The EEAR were prepared in 100% ethanol by cold extraction process. Then, phytochemical screening of the extract was done by several qualitative tests. A total 40 male goats (EPG at least 100) were allocated equally randomly in AR-100, AR-200 and Positive control (P-Ctrl) and Negative control (N-Ctrl) groups. The goats of AR-100, AR-200 and P-Ctrl groups received EEAR at the rate of 100 mg/kg, 200 mg/kg and albendazole 10 mg/kg, respectively. However, normal water was provided to N-Ctrl group. EPG count was assessed by modified Mc-Master technique on day 0, 3, 7, 14 and 28 and FECR% were calculated on these days. Data of EPG count and FECR% were analyzed using One-Way-ANOVA followed by LSD for multiple mean comparisons by using SPSS. Results: Phytochemical screening of EEAR revealed the presence of phytosterol, terpenoids, saponin, glycosides, carbohydrate and reducing sugar. The EPG count was decreased in both extract treated group on the dose dependent manner on day 7, 14, 21 and 28. The FECR% on the extract treated group was increased on dose dependent manner on day 7, 14, 21 and 28. The 100 mg/kg bwt and 200 mg/kg bwt dose of extract showed the maximum FECR% 73.05±2.90 and 87.18±5.41 respectively on day 28. Conclusion: The 200 mg/kg bwt dose of EEAR has sufficient anthelmintic activity against nematodes in goat. Novelty: There was no research on anthelminthic efficacy of EEAR against gastrointestinal nematodes in goat. This research is novel approach for controlling the gastrointestinal nematodes in goat by using the phytoconstituent of AR root. This study scientifically contributes to the animal health and sustainable goat farming.